Progress Towards Laser Wakefield Acceleration and Applications at the Scottish Centre for the Application of Plasma-based Accelerators (SCAPA). (July 2020) - Holt, G K; Battaglia, G; Brunetti, E; Feehan, J; Kornaszewski, A; Li, W; Maitrallain, A; Manahan, G G; Pring, W D; Reid, L R; Shahzad, M; Spesyvstev, R; et al.
Abstract: Laser wakefield accelerators (LWFAs) are promising sources of high brightness particle and radiation beams with many possible applications, ranging from scientific research to medicine, industry and border security. The Scottish Centre for the Application of Plasma-based Accelerators (SCAPA) is a university-based facility employing the use of two high-power, ultrashort pulse lasers to advance research, development and application of laser-plasma accelerators. Here we report on recent advancements in LWFA research at SCAPA and upcoming research programmes to demonstrate proof-of-concept applications of the LWFA.